Pendampingan Pengajaran dan Konservasi Cagar Budaya Masyarakat Desa Adan-Adan Kecamatan Gurah Kabupaten Kediri - Erna Fatmawati; Nara Setya Wiratama; Zainal Afandi; Agus Budianto; Amri Ichsa Ardhana (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2024)
This service article discusses the role of students in community service through teaching and socialization in Adan-Adan Village. This volunteer project demonstrates the value of community service in the context of higher education. This activity includes coaching, teaching, and preserving cultural heritage, with training methods that include planning, implementation, and evaluation stages. Adan-Adan Village conducted community service on March 18, 2024. Teaching activities were conducted at Madrasah Ibtidaiyah Al Falah, SD Negri 1 Adan-Adan, and Taman Pendidikan Al Qur’an Annur. In order to encourage young people to spread the advantages of community service, this community service project aims to develop technological innovations. Community service activities in schools and TPQ can also provide better dedication to improving the quality of learning and teaching and developing student potential. Furthermore, cultural heritage preservation plays a critical role in preserving human cultural heritage and the legitimacy of a community's cultural identity. Therefore, the community is crucial to ensuring that cultural heritage is sustained. The success of this service activity is evident from the students' and the Adan-Adan Village community's active participation in it, according to the questionnaire provided by the service team.